Etika Medis Spiritual-Humanis: Analisis Manhaj Al-Fikr Aswaja dalam Transformasi Rumah Sakit - Fikran Siddik; Hilma Yuniar Thamrin; Sandi Andri Natal Butarbutar (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This research is motivated by the phenomenon of dehumanization and mechanization in modern healthcare, which tends to reduce patient dignity to mere clinical objects. Amidst the current of healthcare commercialization, a philosophical reorientation is required to integrate medical sophistication with human values. This study aims to construct a hospital service paradigm based on the manhaj al-fikr (method of thought) of Ahlussunnah wal Jama’ah (Aswaja). Employing a qualitative research method with a library research approach, this study analyzes the four pillars of Aswaja—tawassuth (moderation), tawazun (balance), i’tidal (justice), and tasamuh (tolerance)—as the foundation for hospital governance. The results indicate that the internalization of these pillars produces a “Spiritual-Humanist” service model. The pillars of tawassuth and tawazun play a role in synthesizing medical technology with spiritual care, while the pillars of i’tidal and tasamuh ensure the enforcement of distributive justice and inclusivity for a pluralistic society. This transformation results in the strengthening of healthcare professionals’ public service motivation and the restoration of public trust in hospitals as healing oases that humanize individuals.